Gerstmann's syndrome and unilateral optic ataxia in the emergency department - Barbosa, Breno José Alencar Pires (Dement Neuropsychol, 2017)
A 75-year-old right-handed woman presented to the emergency department with simultanagnosia and right unilateral optic ataxia. Moreover, the patient had agraphia, acalculia, digital agnosia and right-left disorientation, consistent with complete Gerstmann's syndrome. This case highlights the concurrence of Gerstmann's syndrome and unilateral optic ataxia in the acute phase of a left middle cerebral artery stroke.